PROBLEMS IN FORMATION OF BASIC COMPETENCES OF EDUCATORS IN THE PROCESS OF PREPARATION FOR SCHOOL (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article describes the importance of the formation of basic competencies in the quality and thorough preparation of preschool children for school education, the analysis of information about the harmonious development of preschool children in all aspects.